Evaluation Of Malaria Surveillance System In Department Of Health District Sumbawa Besar - Zainuddin Zainuddin; Lucia Yovita Hendrati (Universitas Airlangga, 2014)
Malaria is one of the public health problems that can affect infant, toddler, or mother mortality rates and can reduce work productivity. The malaria morbidity rate in the Sumbawa district is still high, as seen from the annual parasitic incident from 2008 to 2011. The purpose of this study is to find out the description of the implementation of the Malaria Surveillance System at the Sumbawa Besar District Health Office in West Nusa Tenggara Province. This research uses descriptive survey method. Research subjects were malaria surveillance officers from the Health Office, Public health center (PHC), and Hospitals. The object of the research was the malaria epidemiological surveillance report document in 2013. Data analysis techniques were obtained from interviews and observations that were analyzed descriptively. The results show that at the input stage the type of data is incomplete, the quantity of labor is complete but the quality of labor is not sufficient, facilities and funds are sufficiently available. At the stage of the data collection process using the W2 weekly report and monthly report format, report format and simple reporting flow, completeness of W2 weekly report and monthly report 100%, timeliness of weekly outbreak reports > 80% and monthly reports > 90%, data analysis and interpretation have already done but the relationship analysis is still 20% done by the health center. The output produced in the form of a picture of endemicity of the region, annual parasite incident, and slide positivity rate is presented in tables, graphs, and maps. Dissemination of information is done in the form of reports, workshops, and profiles. Feedback is carried out every month through coordination meetings, regular meetings, and periodic supervision. Evaluation of surveillance systems based on surveillance attributes is simple, acceptable, sensitivity cannot be assessed, the positive predictive value is low 1.75%, report timeliness is > 80%.